2021
DOI: 10.4314/jasem.v25i3.2
|View full text |Cite
|
Sign up to set email alerts
|

Ethanolic Extract of Ground Vernonia Amygdalina Stem Exhibited Potent Antibacterial Activity and Improved Hematological Bio-Functional Parameters in Normal and Monosodium Glutamate-Intoxicated Rats

Abstract: Herein, Vernonia amygdalina stem ethanolic extract, VASEE, was elucidated for its antibacterial activity in vitro by disk-diffusion technique and, in vivo effect on some hematological parameters of normal and monosodium glutamate, MSG-intoxicated rats. For in vivo study, 20 male albino rats assigned into five groups (A, B, C, D, and E) were, for 14 days, respectively administered MSG (8000 mg/kg body weight, bw), VASEE (200 mg/kg bw), Control (Vital feed and tap water), MSG (8000 mg/kg bw + VASEE, 200 mg/kg bw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The determination of the antimicrobial activity of the [16][17][18][19][20] eleven microbial pathogens as reported earlier . This was was based on the disk diffusion technique using 10 mm discs obtained as 50 mg of Ketoconazole (antifungal) and Ciprofloxacin (antibacterial) standard strains.…”
Section: Determination Of Antimicrobial Activities Of Topementioning
confidence: 99%
“…The determination of the antimicrobial activity of the [16][17][18][19][20] eleven microbial pathogens as reported earlier . This was was based on the disk diffusion technique using 10 mm discs obtained as 50 mg of Ketoconazole (antifungal) and Ciprofloxacin (antibacterial) standard strains.…”
Section: Determination Of Antimicrobial Activities Of Topementioning
confidence: 99%
“…Similarly, ethanolic extracts of L. vulgare and V. amygdalina showed a broad-spectrum antimicrobial activity against all the tested pathogens. This could be ascribed to the richness of these extracts in phytochemicals such as saponins, sesquiterpenes, flavonoids, steroid glycosides, and lactones [20] for which recent studies reported its antibacterial activity [21]. Amongst leaves extracts, those derived from M. oleifera were more actives against the bacterial strains E. coli ATCC 25922 and S. aureus ATCC 6538 while extract from L. vulgare leaves was more active against C. albicans ATCC 10231.…”
Section: Inhibition Zone Of Extract Against Tested Bacteriamentioning
confidence: 99%
“…It has also been reported to have antioxidant, anti-inflammatory, antitumor, antimicrobial, hepatoprotective and anti-arthritic properties [14][15][16]. V. amygdalina (known in Cameroon under the popular name of Ndolè) have been reported to have anticancer and antitumor activity [17,18]; antihepatotoxic activity [19]; hypoglycemic activity [20]; antibacterial activity [21]; anti-inflammatory [22] as well as antioxidant property [23]. Moreover, C. citratus (lemongrass) is widely used as a tea and is rich in minerals, vitamins, macronutrients (including carbohydrate, protein, and small amounts of fat) and its leaves are a good source of various bioactive compounds such as alkaloids, terpenoids, flavonoids, phenols, saponins and tannins that confer C. citratus leaves pharmacological properties such as anti-cancer, antihypertensive, anti-mutagenicity, anti-diabetic, antioxidant, anxiolytic, anti-nociceptive and anti-fungal [24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation